Análisis genético en pacientes con cáncer colorrectal (2006)
ABSTRACT: : In patients with colorectal carcinoma, insertions or deletions of short sequences of DNA, a phenomenon called microsatellite instability, are observed. Aim: To look for microsatellite instability and mutations of MLH1 and MSH2 gene mutations in patients with colorectal carcinoma. Material and Methods: Ten patients with sporadic colorectal carcinoma and 31 patients fulfilling criteria for hereditary nonpolyposis colon cancer (HNPCC), aged 9 to 70 years, were studied. Microsatellite instability was studied in samples of tumor and peripheral blood mononuclear cell DNA. Six markers were amplified by polymerase chain reaction and capillary electrophoresis. In samples with microsatellite instability, mutations of MLH1 and MSH2 genes were studied by direct sequencing. Results: Thirty four percent of patients had microsatellite instability and among these, 76% had a high degree of instability. BAT40 marker had the higher frequency of instability. No mutations for MLH1 and MSH2 genes were observed. However a new polymorphism, C399T, was identified in exon 3 of MSH2 gene. This polymorphism was observed both in patients with sporadic colorectal carcinoma and patients with HNPCC. Conclusions: There is a high frequency of microsatellite instability among patients with colorectal cancer. A new polymorphism, not previously reported, was identified in MSH2 gene (Rev Méd Chile 2006; 134: 1221-29).